Convergent synthesis of new N -substituted 2-{[5-(1H -indol-3-ylmethyl)-1,3,4-oxadiazol-2-yl]sulfanyl} acetamides as suitable therapeutic agents - Rubab, Kaniz; Abbasi, Muhammad Athar; Ur-Rehman, Aziz; Siddiqui, Sabahat Zahra; Ashraf, Muhammad; Shaukat, Ayesha; Ahmad, Irshad; Lodhi, Muhammad A.; Khan, Farman Ali; Shahid, Muhammad; Akhtar, Muhammad Nadeem (Faculdade de Ciencias Farmaceuticas (Biblioteca), 2015)
A series of N-substituted 2-{[5-(1H-indol-3-ylmethyl)-1,3,4-oxadiazol-2-yl]sulfanyl} acetamides (8a-w) was synthesized in three steps. The first step involved the sequential conversion of 2-(1H-indol-3-yl) acetic acid (1) to ester (2) followed by hydrazide (3) formation and finally cyclization in the presence of CS2 and alcoholic KOH yielded 5-(1H-indole-3-yl-methyl)-1,3,4-oxadiazole-2-thiol (4). In the second step, aryl/aralkyl amines (5a-w) were reacted with 2-bromoacetyl bromide (6) in basic medium to yield 2-bromo-N-substituted acetamides (7a-w). In the third step, these electrophiles (7a-w) were reacted with 4 to afford the target compounds (8a-w). Structural elucidation of all the synthesized derivatives was done by 1H-NMR, IR and EI-MS spectral techniques. Moreover, they were screened for antibacterial and hemolytic activity. Enzyme inhibition activity was well supported by molecular docking results, for example, compound 8q exhibited better inhibitory potential against α-glucosidase, while 8g and 8b exhibited comparatively better inhibition against butyrylcholinesterase and lipoxygenase, respectively. Similarly, compounds 8b and 8c showed very good antibacterial activity against Salmonella typhi, which was very close to that of ciprofloxacin, a standard antibiotic used in this study. 8c and 8l also showed very good antibacterial activity against Staphylococcus aureus as well. Almost all compounds showed very slight hemolytic activity, where 8p exhibited the least. Therefore, the molecules synthesized may have utility as suitable therapeutic agents.